Size Effect on the Damaged Areas of Glass/Epoxy Structures under Low Velocity Impact - M. Shokrieh; F. Taheri-Behrooz; H. Haftchenari; M. Mozafari (Mechanics of Advanced Composite Structures)
Most impact tests are carried out on specimens with specific stacking sequence and dimensions to meet standard and experimental limitations. The damaged areas and the resulted reduction in the strength values of specimens may not agree very well with those of real application. In this paper an attempt is made to study the variation in the size of damaged areas due to varying the dimension of test specimens. Three different types of specimens, namely, A, B and C are examined under the same impact energy. It is found that the area of damage in the smaller size test specimens is larger. It is also concluded that the mode of failure is different for various specimens. The study of impact energy/damage area reveals that the types B and C tend to agree more than the smaller type suggesting a convergence of results as the specimen size approaches the actual size of larger nature. These graphs may be utilized to find impact energy in real structures with a specific stacking sequence and layout, if the size of damaged area is known.